2016
DOI: 10.1007/s00405-016-3943-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of supraglottoplasty vs. wait-and-see policy in patients with laryngomalacia

Abstract: In most cases, laryngomalacia presents as a mild disease, and the symptoms resolve after wait-and-see policy. Up to 20 % of patients present with severe laryngomalacia and may require surgery (i.e. supraglottoplasty); however, the indication for surgery is not firmly established yet. The goal of this study is to determine whether supraglottoplasty results in a better outcome than wait-and-see and to investigate how different comorbidities influence outcome. A retrospective study of pediatric cases of in a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
0
13
0
4
Order By: Relevance
“…17 Additionally, supraglottoplasty in Dutch children with LM was found to result in complete resolution of symptoms by 5 weeks compared to 29 weeks in those patients with LM who underwent observation. 18 Despite numerous analyses composed of institutional retrospective cohorts and single-surgeon reports, there has been limited research effort toward evaluating the perioperative sequelae of children undergoing surgery for LM from a national perspective.…”
Section: Introductionmentioning
confidence: 99%
“…17 Additionally, supraglottoplasty in Dutch children with LM was found to result in complete resolution of symptoms by 5 weeks compared to 29 weeks in those patients with LM who underwent observation. 18 Despite numerous analyses composed of institutional retrospective cohorts and single-surgeon reports, there has been limited research effort toward evaluating the perioperative sequelae of children undergoing surgery for LM from a national perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term data could have assessed for normalizations of QOL outcomes with the general population; however, literature has shown that laryngomalacia typically takes months to resolve without supraglottoplasty whereas complete symptomatic improvement with supraglottoplasty occurs over the course of weeks. 38 It stands to reason that as our data show improvement in QOL along a timeline similar to functional improvements following supraglottoplasty, the improvement in QOL is likely secondary to undergoing supraglottoplasty rather than bias or the natural history of the disease. The ITQOL-SF47 itself is limited in that it relies on parental perceptions and not actual patient-reported or objective information.…”
Section: Discussionmentioning
confidence: 59%
“…A similar retrospective study, of 89 patients, compared outcomes of supraglottoplasty with those of a wait-and-see policy, and considered the influence of co-morbidities 20 . Unsurprisingly, surgery was associated with a statistically significant faster resolution of symptoms than conservative management (5 weeks vs 29 weeks; p = 0.026), and synchronous airway lesions further prolonged symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, surgery was associated with a statistically significant faster resolution of symptoms than conservative management (5 weeks vs 29 weeks; p = 0.026), and synchronous airway lesions further prolonged symptoms. The authors found supraglottoplasty to be safe and effective in severe laryngomalacia, but did concede that ‘the indication for surgery is not firmly established yet’ 20 …”
Section: Discussionmentioning
confidence: 99%